The role of geopolitical factors in neighboring countries and regional powers in the continuation of the Afghanistan crisis - Nazari, Nizamuddin; Noori, Abdul Muswer Sias (Technium Social Sciences Journal, 2022)
Afghanistan has at times faced crises, mostly due to the interference of hostile countries in all affairs of the country. The crises in Afghanistan, at any time, from the interventions of the countries of the region and the rivalry of the great supra-regional and global powers that have caused the crisis in this country to continue, especially in recent decades, which has led to many tensions. Investigating why this country is in crisis requires recognizing its contexts and underlying factors. Global regional and trans-regional factors are the root causes, sustainability and context that need to be examined. The present study seeks to study, analyze and find the root of the crisis of this country from a geopolitical point of view with a descriptive-analytical method. And the area has been surveyed. Findings show that neighboring countries and the region, especially the above factors, have a role to play in the recent crises in Afghanistan, as well as the competition of powers, both domestically and nationally, as well as regionally, trans regionally and globally. Have played an effective role in the crisis in this country and have caused the crisis in Afghanistan to continue.